Aplikasi To-Do List Berbasis Android dengan MIT App Inventor - Nurul Hidayati, Sularno (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2024)
programming platform designed to facilitate app development for individuals with minimal programming knowledge. The main features of the application include adding, saving, updating, removing, and clearing all tasks, providing users with essential tools for effective task management. The purpose of this study is to demonstrate the feasibility of developing a functional to-do list application using MIT App Inventor, highlighting its potential as a rapid prototyping tool for beginners and educators. The research method involves a comprehensive process starting from designing the user interface, implementing the application logic, conducting rigorous functional testing, and gathering user feedback to ensure the application meets user needs. The user interface design focuses on simplicity and ease of navigation to ensure that users can interact with the application intuitively. The implementation leverages MIT App Inventor's block-based coding system to develop the core functionalities of the application. Functional testing is performed to verify that all features operate correctly, and user feedback is collected through surveys and interviews to evaluate the application’s effectiveness and usability. The results of this research indicate that the application is effective in helping users manage their tasks efficiently. Users, particularly those without a technical background, found the application easy to use and beneficial for organizing their daily activities. The study concludes that MIT App Inventor is a valuable tool for developing simple yet functional mobile applications and can be an excellent educational resource for teaching basic programming concepts. This research contributes to the understanding of how visual programming platforms can democratize app development and provide practical tools for everyday task management.